IMPLEMENTATION OF A TRAINING PROGRAM TO DETERMINE NUTRITIONAL STATUS FOR POSYANDU CADRES BASED ON TECHNOLOGY AND INFORMATICS DEVELOPMENT - Sudiyono, Sudiyono (Yayasan Meira Visi Persada, 2024)
This study aims to explore the potential implementation of a training program in determining the nutritional status of Posyandu cadres by leveraging technological and informatics developments. The developed training program involves aspects of technological and informatics development, including the use of mobile applications, specialized software, and online resources. The research results indicate that the implementation of this training program positively contributes to enhancing the knowledge of Posyandu cadres in determining the nutritional status of children and mothers. Furthermore, the integration of technology and informatics facilitates the collection, analysis, and reporting of nutritional data, improving the efficiency and accuracy of information. The implementation of this training program is expected to serve as a model applicable to various Posyandu, utilizing technological advancements to enhance the quality of community health services. Practical implications of this research include the enhancement of skills and knowledge among Posyandu cadres, as well as the increased effectiveness of nutritional monitoring programs. Thus, this study provides a foundation for further development in utilizing technology and informatics to improve the nutritional status of communities at the local level.